Successful Unrelated Cord Blood Stem Cell Transplantation in an X-linked Chronic Granulomatous Disease Patient with Disseminated BCG-induced Infection - Chao-Jen Lin; Shih-Chung Wang; Cheng-Lung Ku; Jun-kai Kao; Ming Chen; Chin-San Liu (Elsevier, 2015)
A 19-month-old boy with chronic granulomatous disease (CGD) received umbilical cord blood transplantation (UCBT) from an unrelated donor after experiencing a life-threatening disseminated Bacillus Calmette-Guérin infection. After busulfan and cyclophosphamide conditioning, we performed a 5/6-matched UCBT. Engraftment and mixed chimerism was 100% in peripheral blood, and 100% of his neutrophils had normal oxidative burst activity on day 17. The patient is now 3 years old, free from infection, and growing well. To our knowledge, this is the second case of CGD treated with UCBT in Taiwan. His successful outcome illustrates that UCBT in a patient with CGD should be considered early if a human leukocyte antigen-matched donor is not available or the patient has just recovered from a severe infection.